1H‐NMR with Multivariate Analysis for Automobile Lubricant Comparison1. Issue 4 (23rd February 2017) - Kim, Siwon; Yoon, Dahye; Lee, Dong‐Kye; Yoon, Changshin; Kim, Suhkmann
Abstract: Identification of suspected automobile‐related lubricants could provide valuable information in forensic cases. We examined that automobile lubricants might exhibit the chemometric characteristics to their individual usages. To compare the degree of clustering in the plots, we co‐plotted general industrial oils that were highly dissimilar with automobile lubricants in additive compositions. 1 H‐NMR spectroscopy was used with multivariate statistics as a tool for grouping, clustering, and identification of automobile lubricants in laboratory conditions. We analyzed automobile lubricants including automobile engine oils, automobile transmission oils, automobile gear oils, and motorcycle oils. In contrast to the general industrial oils, automobile lubricants showed relatively high tendencies of clustering to their usages. Our pilot study demonstrated that the comparison of known and questioned samples to their usages might be possible in forensic fields.